Physiological maturity and drying speed in the quality of zucchini ( Cucurbita pepo L.) seeds - Silva,Hellismar Wakson da (2017)
Abstract: Harvesting and drying are essential procedures to obtain high quality seeds as well as for their conservation during storage. The goal of this research was to identify the physiological maturity stage and to verify the effect of drying speeds on the quality of zucchini seeds. A completely randomized design in a 3x2x2 factor scheme was used, involving three fruit maturation stages (49, 56 and 63 days after anthesis - DAA), two drying speeds (slow and quick) and two storage periods (0 and 6 months). Seed quality was evaluated by germination, first count, accelerated aging, electrical conductivity, tetrazolium, seedling emergence, emergence speed index and seed health test. Moisture content, thousand seed mass and percentage full seeds were also evaluated. Zucchini seeds reach maximum quality at 49 DAA. Slow or quick drying and storage do not affect the physiological quality of seeds that were harvested at 49 DAA. The delayed harvest of fruits reduces the quality of seeds. Quick drying reduces the incidence of the fungi Alternaria, Cladosporium, Phoma and Fusarium, and increases the occurrence of Aspergillus and Penicillium.